Magnetic Records of Extreme Geological Events - Eric Font (Frontiers Research Topics, 2017)
Recent advances in environmental magnetism offer the opportunity to link the magnetic signature of marine and continental rocks to the paleoenvironmental and paleoclimatic settings that controlled their formation or deposition, as well as to post-depositional events, such as diagenesis, that can alter their primary signature. This Research Topic assembles studies that used state of the art rock magnetic techniques to unravel the causes and effects of catastrophic geological events, including tsunami, meteorite impacts, Archean oxygenation event, geomagnetic reversals, and global climate changes linked to large volcanic eruptions.